An evaluation framework for cross‐platform mobile application development tools. (27th August 2014) - Dhillon, Sunny; Mahmoud, Qusay H.
Summary The mobile application market is becoming increasingly fragmented with the availability of multiple mobile platforms that differ in development procedures. Developers are forced to choose to support only some platforms and specific devices because of limited development resources. To address these challenges, numerous tools have been created to aid developers in building cross‐platform applications; however, there is no metric to evaluate the quality of these tools or the applications produced by them. This paper introduces a framework for evaluating the features, performance, and development experience of existing and future cross‐platform development tools. The framework is implemented by benchmarking several tools, and the results identify a disparity in the features and performance of applications built using different development tools. Copyright © 2014 John Wiley & Sons, Ltd.